How to Find a Book - StJohn, Amanda; Ostrom, Bob (New York : AV2 by Weigl, 2018)
Stew Rabbit learns how to find books using the library catalog with help from the children's librarian, Miss Mantis.
Keywords: Online library catalogs -- Juvenile literature; Books -- Juvenile literature; Children's libraries -- Juvenile literature; Public libraries -- Juvenile literature